7,8-Dihydroxyflavone is a direct inhibitor of human and murine pyridoxal phosphatase - Brenner, Marian; Zink, Christoph; Witzinger, Linda; Keller, Angelika; Hadamek, Kerstin; Bothe, Sebastian; Neuenschwander, Martin; Villmann, Carmen; von Kries, Jens Peter; Schindelin, Hermann; Jeanclos, Elisabeth; Gohla, Antje (eLife, 2024)
Vitamin B6 deficiency has been linked to cognitive impairment in human brain disorders for decades. Still, the molecular mechanisms linking vitamin B6 to these pathologies remain poorly understood, and whether vitamin B6 supplementation improves cognition is unclear as well. Pyridoxal 5’-phosphate phosphatase (PDXP), an enzyme that controls levels of pyridoxal 5’-phosphate (PLP), the co-enzymatically active form of vitamin B6, may represent an alternative therapeutic entry point into vitamin B6-associated pathologies. However, pharmacological PDXP inhibitors to test this concept are lacking. We now identify a PDXP and age-dependent decline of PLP levels in the murine hippocampus that provides a rationale for the development of PDXP inhibitors. Using a combination of small-molecule screening, protein crystallography, and biolayer interferometry, we discover, visualize, and analyze 7,8-dihydroxyflavone (7,8-DHF) as a direct and potent PDXP inhibitor. 7,8-DHF binds and reversibly inhibits PDXP with low micromolar affinity and sub-micromolar potency. In mouse hippocampal neurons, 7,8-DHF increases PLP in a PDXP-dependent manner. These findings validate PDXP as a druggable target. Of note, 7,8-DHF is a well-studied molecule in brain disorder models, although its mechanism of action is actively debated. Our discovery of 7,8-DHF as a PDXP inhibitor offers novel mechanistic insights into the controversy surrounding 7,8-DHF-mediated effects in the brain.
Keywords: vitamin B6; cognition; pyridoxal phosphatase; pyridoxal phosphatase inhibitor; 7,8-dihydroxyflavone; X-ray crystal structure